2021
DOI: 10.5755/j01.ee.32.3.28360
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 Pandemic and Independent Convenience Stores in the United Kingdom

Abstract: Covid-19 brought the new reality into every-day life, global economy, and various sectors, including independent convenience stores. After the first and during the second wave of Coronavirus in the United Kingdom (mid-November 2020), the overall situation was very dynamic and turbulent. This paper is thus aimed at answering the question how the independent convenience stores sector in the United Kingdom functions in the Covid-19 reality. We analyse such issues as the recession phase in the global economy, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…In addition to these anecdotal case reports, there are also a growing (yet limited) number of studies using microlevel survey data to investigate the dynamics and heterogeneities of consumers’ buying behaviors ( Ellison et al, 2020 , Gao et al, 2020 , Moon et al, 2021 , Wang and Na, 2020 ) and of enterprises’ reaction behaviors ( Rybaczewska et al, 2021 , Dannenberg et al, 2020 , Mahajan and Tomar, 2020 , Priambodo et al, 2021 ; Shafi et al, 2020). Studies about consumers’ purchasing behaviors based on internet survey data from a few hundred consumers have generally found that the occurrence of COVID-19 and its subsequent control measures have encouraged the shift of consumers’ purchasing behaviors of food from offline to online channels worldwide (e.g., Chenarides et al, 2021 , Ellison et al, 2020 on U.S., Wang and Na, 2020 , Gao et al, 2020 on China; Mehrolia, et al 2020 on India, Moon et al, 2021 on Korea).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these anecdotal case reports, there are also a growing (yet limited) number of studies using microlevel survey data to investigate the dynamics and heterogeneities of consumers’ buying behaviors ( Ellison et al, 2020 , Gao et al, 2020 , Moon et al, 2021 , Wang and Na, 2020 ) and of enterprises’ reaction behaviors ( Rybaczewska et al, 2021 , Dannenberg et al, 2020 , Mahajan and Tomar, 2020 , Priambodo et al, 2021 ; Shafi et al, 2020). Studies about consumers’ purchasing behaviors based on internet survey data from a few hundred consumers have generally found that the occurrence of COVID-19 and its subsequent control measures have encouraged the shift of consumers’ purchasing behaviors of food from offline to online channels worldwide (e.g., Chenarides et al, 2021 , Ellison et al, 2020 on U.S., Wang and Na, 2020 , Gao et al, 2020 on China; Mehrolia, et al 2020 on India, Moon et al, 2021 on Korea).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Cuenca Garcia et al (2013) highlight the importance of institutional approach to tax systems analysis. Rybaczewska et al (2021) argue that Covid-19 pandemic has brought many uncommon and unexpected by entrepreneurs or citizens of the CEECs, regulations. These regulations are impossible to predict and hard to identify.…”
Section: Literature and Hypotheses Developmentmentioning
confidence: 99%
“…It is also relatively resilient during the pandemic when various challenges for business functioning are observed, including supply chains disruptions, panic buying, uncertainty connected with Brexit etc. (ACS & SGF, 2021; Billore & Anisimova, 2021;Rybaczewska, Sułkowski & Bilan, 2021). Convenience stores, being in the heart of their local communities, are strongly connected with the local economy (e.g.…”
Section: Grocery Shopping Behaviour and Convenience Store Sectormentioning
confidence: 99%
“…This brings questions about the average basket spend. The convenience store sector may be perceived as resilient during Covid-19 (Rybaczewska, Sułkowski, & Bilan, 2021) thanks to increased number of customers or higher average basket spend. To verify all these in the context of three devolved nations of the mainland UK we formulate two hypotheses:…”
Section: Grocery Shopping Behaviour Shifts In the Era Of Covid-19mentioning
confidence: 99%